(untitled) (Web of Teachers: Inderscience Research, 2023)
The global spread of English over the last 50 years is remarkable. It is unprecedented in several ways: by the increasing number of users of the language; by its depth of penetration into societies; by its range of functions. English is found on every continent. It has major speech communities in over seventy countries. It is the language of the internet. It is language of air-traffic control, of international travel, international business and science.